Analisis Tindak Tutur Ilokusi Ekspresif dalam Anime Horisan to Miyamurakun Episode 1 - Uerika Vani Juniarti; Amelya Septiana (Universitas Negeri Jakarta, 2026)
This study aims to analyze the expressive illocutionary acts that occur in the interactions between characters in the anime Hori-san to Miyamura-kun episode 1. Expressive illocutionary acts, which emphasize the expression of the speaker's feelings and emotions, are crucial in portraying the development of relationships among the characters throughout the story. As outlined in John Searle's speech act theory, this research identifies various types of emotional expressions conveyed by Hori and Miyamura, such as gratitude, apologies, praise, and complaints. The data were obtained by analyzing key dialogues in the episode 1 of the anime. The findings reveal that expressive speech acts play a vital role in character development, strengthening emotional connections between characters, and providing a deeper understanding of the emotional dynamics among them. This study is expected to contribute to the understanding of the use of speech acts in fictional media, particularly anime, as a tool to depict the complexity of human emotions.